2021
DOI: 10.20473/jipk.v13i1.23085
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Filopaludina javanica and Sulcospira testudinaria in Reducing Organic Matter in Catfish (Clarias sp.) Aquaculture Wastewater

Abstract: HighlightCatfish aquaculture wastewater contains organic matter that exceeds the quality standard of 68.75 mg / L and 72.48 mg / L.Tutut Jawa snail (F. javanica) can reduce organic matter in waste by up to 92%.Susuh Kura snail (S. testudinaria) can reduce organic matter in waste by up to 87%.Catfish aquaculture wastewater treatment with snails only takes 8 hours. Abstract The residual or wastewater from the cultivation process that is discharged directly into common waters can reduce the quality of the waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous research found that Sulcospira testudinaria was present in the Cikeruh River [Lutfi et al, 2020], Code River [Hellen et al, 2020], Meru Betiri National Park [Suratno et al, 2020], Gunung Kidul [Isnaningsih and Listiawan, 2010], and the Brantas River [Febbyanto et al, 2015]. This species was used as a bioindicator for aquatic environmental health [Hertika et al, 2021], and was used to measure the results of efforts to reduce levels of organic matter in aquaculture wastewater [Lailiyah et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that Sulcospira testudinaria was present in the Cikeruh River [Lutfi et al, 2020], Code River [Hellen et al, 2020], Meru Betiri National Park [Suratno et al, 2020], Gunung Kidul [Isnaningsih and Listiawan, 2010], and the Brantas River [Febbyanto et al, 2015]. This species was used as a bioindicator for aquatic environmental health [Hertika et al, 2021], and was used to measure the results of efforts to reduce levels of organic matter in aquaculture wastewater [Lailiyah et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…Further, F. m. martensi has been suggested (along with Filopaludina javanica von dem Busch 1844 and Sulcospira testudinaria von dem Busch 1842) as a way to reduce the total organic matter content from organism faeces and feed residue during catfish (Clarias sp.) and Nile tilapia culture (Jiwyam et al, 2008;Lailiyah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%